Liouville theorems in unbounded domains for the time-dependent stokes system - Jia, H; Seregin, G; Sverak, V (2012)
In this paper, we characterize bounded ancient solutions to the time-dependent Stokes system with zero boundary value in various domains, including the half-space. © 2012 American Institute of Physics.